Types of `reticulin' antibodies detected in human sera by immunofluorescence - Rizzetto, Mario (1973)
Reticulin antibodies have been classified by immunofluorescence into five types reacting with distinct antigens of intra- and extracellular components in mesenchyme. Two types of fibrillar antigens can be distinguished on the basis of the staining patterns, anatomical distribution, and species specificity. A third antibody reacts with either small fibres, amorphous proteins, or mucopolysaccharides lining the hepatic sinusoids (ground substance antigens). In addition, at least two kinds of intrasinusoidal cells show cytoplasmic fluorescence, ie, Kupffer cells and glass-adherent, blood-borne cells antigenically related to peritoneal macrophages. Some sera may contain antibodies reacting with sinusoidal endothelial cells though this has not yet been proven. It has been confirmed that all these distinct antibodies related to reticulin antigens are most frequent in dermatitis herpetiformis and coeliac disease, but they are also found with increased frequency in chronic heroin addicts and in rheumatoid and Sjögren's syndromes. About 5% of normal individuals had such antibodies and no significant increase could be demonstrated in autoimmune disorders or in liver cirrhosis. The antibodies appear to be stimulated by bacterial or nutritional antigens and are likely to represent anamnestic responses rather than direct cross reactions with a multiplicity of foreign antigens.